USING PROGRAMMING APPLICATION TO SOLUTION THE DIFFICULT AWARD OF CONTRACTS (SUPPLIED- CONSTRUCTION) (Journal of Engineering, 2010)
The research aims to use the computer and it's potential to identify and choose the best offers submitted by companies contracting with the third-expected increases in the wages of labor and prices of building materials and the large variability in the impact of the inability of many of the construction to complete the implementation of the specific time or the estimated cost and thus create a lot of problems executive, which affected the speed and quality of works. A good management and good planning through implementation to reflect the realities and possibilities of each of the contracting companies to tender for any contract so a knowledge of possibilities of each company and compare it with the other , according to the mechanism in the desired implementation , depending on the nature of each project if we were able to optimize( cost , duration , quality ) the selection of the presentations developed by the companies and thus the achievement of the project , including and appraiser of the cost , quality and needed time . The research has dealt with the items and factors of success of the trade-off between the companies to choose the best offer depending on the factors instrumental to the selection and identification of a percentage and in accordance with the increases Field of personal interviews with many of the professionals and the process of opening and analysis of tenders and the number of software made in the hands of the user the best way to differentiate between companies on the basis of cost or duration , or the quality and efficiency of the company , calculated in accordance with the factors previously or by including the budget allocated according to percentage of each individual of items ( cost , duration , quality ) and by political department raised the auction and the type of project , as well as to identify the type of auction is it a construction or the establishment .